Effect of Hot Air Drying on Ultrastructure of Crambe Seeds - Donadon, Juliana Rodrigues; Resende, Osvaldo; de Teixeira, Simone Pádua; Santos, Jaime Maia dos [UNESP]; Moro, Fabíola Vitti [UNESP] (Taylor & Francis, 2013)
This study was conducted to evaluate the morphologic modifications in tissues of the fruit and seed of the crambe (Crambe abyssinica Hochst. Ex R.E. Fr.) after drying at different temperatures. Fruits with a water content of 0.38 kg water/kg dry matter were harvested and manually homogenized. Drying was accomplished at 35, 45, 60, 75, and 90°C and at 21,9,7,5, and 2% relative humidity, respectively. After drying, the structure of the pericarp and tegument of the seed were evaluated and the embryo was removed from the fruit/seed for morphological analysis (structural and ultrastructural and the histolocalization of reserve substances). Drying at different temperatures did not affect the cellular structure of the tissues composing the pericarp of the fruits, but it disorganized the structure of the seed tegument. The cells of the tegument and cotyledons presented a contraction in their volumes. The lowest contractions in the cellular volumes of both the tegument and cotyledons occurred after drying at 35 and 45°C. The cytoplasm of the cotyledon cells contains oil drops and the protein bodies contain protein granules and starch grains. There were no changes in the cellular walls of the embryos of the fruits dried at different temperatures; however, ungluing of the medium lamella occurred. This damage occurred with greater intensity after drying at temperatures above 60°C. The form of the oil drops in the cytoplasm of the cotyledon cells was altered after drying. At temperatures above 60°C, the drops broke up and coalesced. After drying at 45 and 60°C, the form of some protein bodies was altered, whereas at 75 and 90°C coalescence of the protein bodies occurred in some cells. It was concluded that the identified alterations can affect the physiologic quality of crambe seeds. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Crambe; Dehydration; Scanning electron microscopy; Transmission electron microscopy; Cellular structure; Dry matters; Hot air drying; Morphological analysis; Oil drops; Protein bodies; Cells; Coalescence; Cytology; Drops; Fruits; Histology; Proteins; Tissue; Drying